Aplicativo android com portal web para acompanhamento e divulgação de preços de produtos - Stangherlin, Maicon (2017)
The use of Internet for commercial purposes has grown exponentially, and can be said that buying products online is common in many countries.This work presents the development of a mobile application to dissemination and monitoring of prices, allowing customers to easily visualize item price changes, using the QR Code.For the development of the project, was made use offrameworks that help from the visual part to the layers of persistence, and clientserver communication.The Android platform was used to develop the mobile application. This platform uses Java.As result, a mobile application was developed and the defined requirements were fulfilled. The frameworks used were useful to develop the project.